2009
DOI: 10.1097/mpa.0b013e3181825c00
|View full text |Cite
|
Sign up to set email alerts
|

Total Pancreatectomy With and Without Islet Cell Transplantation for Chronic Pancreatitis

Abstract: Total pancreatectomy is effective in reducing pain and dependence on opioid analgesia in patients with chronic pancreatitis. The addition of an islet cell transplant results in a reduction in 24-hour insulin demands, as well as potentially achieving insulin independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 31 publications
(21 reference statements)
2
97
0
1
Order By: Relevance
“…Notably, the duration of chronic pancreatitis before treatment was not recorded in any of the included studies. Apart from clinical criteria, computed tomography, magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography were used in the preoperative assessment of severity and grading of chronic pancreatitis in most studies 10,12,14 . Two studies reported the patients' preoperative morphine requirement 12,14 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the duration of chronic pancreatitis before treatment was not recorded in any of the included studies. Apart from clinical criteria, computed tomography, magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography were used in the preoperative assessment of severity and grading of chronic pancreatitis in most studies 10,12,14 . Two studies reported the patients' preoperative morphine requirement 12,14 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been shown that purification decreases the number of islets recovered and at least 40 per cent of islet cell mass is lost during purification 14 . Ong and co-workers 28 reported that islet purification is not a compulsory step, and purification should be weighed against wastage of islet cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Garcea et al reported lower HbA1c in the islet cell group [18]. Although there was no statistical significance between the islet and nonislet groups, patients receiving IAT had a significantly lower insulin requirement for a long time (60 months), the detail data was shown in their previous article [19]. C-peptide level at 6 month was reported by two studies with mean being 1.7 ng/mL (SD 0.57 ng/mL) [12], 1.4 ng/mL (SD 0.36 ng/mL) [14], respectively.…”
Section: Metabolic Outcomesmentioning
confidence: 87%